Effectiveness of Preoperative Incentive Spirometry in Patients Following Elective Thoracotomy for Prevention of Postoperative Pulmonary Complication - Sylvia Noviani Saing; Gama Satria; Bermansyah; Irfannuddin (Sriwijaya Journal of Surgery, 2021)
Background: Thoracotomy can cause postoperative impairment of respiratory function and highly risk turns as Postoperative Pulmonary Complication (PPC). One of strategies to decrease risk of PPC in preoperative evaluation is lung expansion maneuvers include Incentive Spirometry (IS). Incentive Spirometry was breathing technique that sustained maximal inspiration, using device which give visual feedback. This study aims to know effectiveness of using preoperative IS in reducing incidence of PPC in thoracotomy patients. Methods: Experimental study with post test only design. Comparing emerged PPC with Melbourne Group Scale Version 2 (MDG-2) criteria in elective posterolateral thoracotomy patients who given IS and non IS preoperative. Data were analyzed using chi square test. Results: Total samples was 32 patients. There was 11 patients had PPC, which 6 recieved IS preoperatively. There was no relation between PPC with age, sex, height, smoking history proportion (p value>0,05). Chi square test showed there was no relation between using IS preoperative and PPC incidence(p>0,710). Conclusions: IS preoperative was not effective in preventing PPC in elective thoracotomy patients.